SARS-CoV-2 seroprevalence in pregnant women in Kilifi, Kenya from March 2020 to March 2022 - Koech, Angela; Omuse, Geoffrey; Mugo, Alex G.; Mwaniki, Isaac G.; Mutunga, Joseph M.; Mukhanya, Moses W.; Wanje, Onesmus; Mwashigadi, Grace M.; Katana, Geoffrey G.; Craik, Rachel; von Dadelszen, Peter; Le Doare, Kirsty; et al. (Frontiers in Public Health, 2023)
Seroprevalence studies are an alternative approach to estimating the extent of transmission of SARS-CoV-2 and the evolution of the pandemic in different geographical settings. We aimed to determine the SARS-CoV-2 seroprevalence from March 2020 to March 2022 in a rural and urban setting in Kilifi County, Kenya.We obtained representative random samples of stored serum from a pregnancy cohort study for the period March 2020 to March 2022 and tested for antibodies against the spike protein using a qualitative SARS-CoV-2 ELISA kit (Wantai, total antibodies). All positive samples were retested for anti-SARS-CoV-2 anti-nucleocapsid antibodies (Euroimmun, ELISA kits, NCP, qualitative, IgG) and anti-spike protein antibodies (Euroimmun, ELISA kits, QuantiVac; quantitative, IgG).This is a provisional file, not the final typeset article A total of 2,495 (of 4,703 available) samples were tested. There was an overall trend of increasing seropositivity from a low of 0% [95% CI 0 -0.06] in March 2020 to a high of 89. in Feb 2022. Of the Wantai test-positive samples, 59.7% [95% CI 57.06 -62.34] tested positive by the Euroimmun anti-SARS-CoV-2 NCP test and 37.4% [95% ] tested positive by the Euroimmun anti-SARS-CoV-2 QuantiVac test. No differences were observed between the urban and rural hospital but villages adjacent to the major highway traversing the study area had a higher seroprevalence.Anti-SARS-CoV-2 seroprevalence rose rapidly, with most of the population exposed to SARS-CoV-2 within 23 months of the first cases. The high cumulative seroprevalence suggests greater population exposure to SARS-CoV-2 than that reported from surveillance data.